Влияние давления на структуру слоя контактного взаимодействия сплавов систем Co–Fе–WC, Co–Fе–TaC и Co–Fе–NbC с графитом - Боримский, А.И.; Делеви, В.Г.; Нагорный, П.А.; Чипенко, Т.Ю. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Special features of the influence of W, Ta and Nb on the interaction between the Co–Fe alloy and graphite at Т = 1600 K and pressure of 4–5 GPа have been studied. It is shown that a pressure increase up to 5 GPа changes the pattern of the influence of W, Ta and Nb on the structure of
the contact melting layer changing it from stable state (solid solution + graphite) to metastable
state (solid solution + Ме3С carbide).